Climate change and agrarian struggles: an invitation to contribute to a JPS Forum. Issue 1 (2nd January 2022) - Borras Jr., Saturnino M.; Scoones, Ian; Baviskar, Amita; Edelman, Marc; Peluso, Nancy Lee; Wolford, Wendy
ABSTRACT: This essay introduces and invites contributions to a new Journal of Peasant Studies Forum on 'climate change and critical agrarian studies'. Climate change is inextricably entwined with contemporary capitalism, but how the relationship between capitalism and climate change plays out in the rural world requires deeper analysis. In particular, the way agrarian struggles connect with the huge challenge of climate change is a vital focus for both thinking and action. In this essay, we make the connections between climate change and critical agrarian studies and identify competing, although overlapping, narratives. These narratives frame climate change debates and the way that the dynamics of climate change shape and are shaped by the rural world, whether through state policies, international governance, corporate influence, or agrarian struggles. We use a simple framework to examine different logics and strategies for anti-capitalist struggles that might connect climate change and agrarian mobilisations. We conclude with some overall reflections and suggestions for broad, guiding questions for future inquiry as part of the JPS Forum.